Road-side Dog jako „przepisanie” Pieska przydrożnego, czyli jak Czesław Miłosz przedstawia sam siebie czytelnikowi amerykańskiemu / Road-side Dog as “rewriting” of Piesek przydrożny or: How Czesław Miłosz presents himself to American readers - Gomola, Aleksander (Przekłady Literatur Słowiańskich, 2019)
The article explores André Lefevere’s rewriting / refraction perspective in literary translation on the basis of the Polish and English versions of Czesław Miłosz’s book Piesek Przydrożny (Road-side Dog). Differences between the original and its translation identified in the analysis suggest that Road-side Dog may be seen as a Lefeverian “rewriting” of the original and as such it both confirms and strengthens a unique position of Miłosz and his oeuvre in American literary system.